Wear resistance of reaction sintered alumina/mullite composites - Luo, H; Zhang, F; Roberts, S (2008)
Alumina and alumina/mullite composites with mullite content of 0.96-8.72 vol.% were subjected to an abrasive wear test under loads of 0.1-2.0 N with a ball-on-disc apparatus. The wear rate and area fraction of pullout fpo on the worn surfaces were measured. The wear resistances of the alumina/mullite composites were better by a factor of 1-2 than that of pure alumina. The main wear mechanism of alumina is fracture wear, and for alumina/mullite composites, fracture wear and plastic wear mechanisms work together. The influence of mechanical properties on wear resistance was estimated by Evans' method. It was found that the wear rate depends on fpo, and the primary reason for the better wear resistance of alumina/mullite composites is the reduction of fpo induced by fracture mode transition. © 2007 Elsevier B.V. All rights reserved.